IMPLEMENTATION OF CLINICAL PHARMACY SERVICE STANDARDS IN HOSPITAL PHARMACY INSTALLATIONS - Rahman, Sartia; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT Hospital pharmacy services are an inseparable part of the hospital health care system. Clinical pharmacy services are services that interact with patients directly with the help of other health teams to improve the quality of drug therapy. This study aims to determine the description of the implementation of clinical pharmacy service standards in Bhayangkara TK III Kendari Hospital. The research method is descriptive observational using a survey design involving secondary data of clinical pharmacy services at Bhayangkara TK III Kendari Hospital. The results showed that in 2021 about tracing the history of drug use 0.4%, counseling 0.006%, 100% visite prescription assessment 0%, Therapeutic Drugs Monitoring 0%, Evaluation of Drug Use 0%, Monitoring Drug Side Effects 0%, Monitoring Blood Drug Levels 0%. In 2022, there was an increase with the results of tracing the history of drug use 0.2%, counseling 0.2%, 88.9% visite prescription review 0%, Therapy Drug Monitoring 0%, Drug Use Evaluation 0%, Monitoring Drug Side Effects 0%, Monitoring Blood Drug Levels 0%. In 2023 it can be reported that the results of tracing the history of drug use are 0.6%, counseling 0.01%, 100% prescription review, visite 0.02%, Therapy Drug Monitoring 0%, Drug Use Evaluation 0%, Monitoring Drug Side Effects 0.03%, Monitoring Blood Drug Levels 0%. The study concluded that the implementation of clinical pharmacy service standards at Bhayangkara Hospital TK III Kendari was still low. Based on the results of this research, it can be suggested that the hospital can tighten the implementation of monitoring evaluation of the implementation of clinical pharmacy standards. Keywords: Clinical Pharmacy; Service Quality, Pharmacy Service Standards